The Effect of the Talking Stick Method on Students’ Speaking Skills in Arabic Language Learning of Grade VIII Students at MTs Al-Amien Putri 1 - Zamilatul Fitriyah; Luthfatul Qibtiyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
Speaking skills are very important in learning Arabic. However, until now many students have difficulty speaking with Arabic language, because speaking skills must be based on confidence to be able to express and speak correctly and well. The purpose of this study was to determine whether there is an influence and how much influence the Talking Stick Method on students' speaking skills in learning Arabic. This study uses a quantitative approach. The research was conducted in class VIII A MTs. Al-Amien Putri 1 with a population of 34 students. Data collection techniques used in this study, there are three methods, namely questionnaires, observation and documentation. The data analysis technique in this study is a simple linear regression test with the help of a Statistical Package For Social Science (SPSS) For Windows versi 16.0. Based on the research results indicate that F count = 7,548 with a significance level of 0,010 < 0,05, it can be seen that there is a significant influence between the Talking Stick method variable (X) on the speaking skill variable (Y).